Not Donne, but Byron: American Criticism and the Mid-Century Classroom. Issue 1 (June 2017) - Rovee, Christopher
Abstract : This essay reassesses Byron's academic reception in mid twentieth-century America. Starting with the American New Criticism's well-known disregard for Byron, the essay illuminates a prominent tension between formal and historical approaches to Byron that was symptomatic of shifts taking place within the profession at large. The essay then draws on archival materials related to the new-critical teaching of Byron, adding a new dimension to prevailing stories about the rise of modern literary studies. Throughout, the essay argues for a more nuanced understanding not only of Byron's mid-century reception but of the sharply intrinsic turn that we tend to associate with the formative years of the discipline.